Right to an Effective Remedy of Legal Protection: Practice of the European Court of Human Rights and the Norms of the National Legislation of Ukraine - KHOMENKO, Mykhailo M.; KOSTRUBA, Anatoliy V.; KOT, Oleksii O. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The article investigates right to effective remedy in the practice of European Court of Human Rights and national courts of Ukraine. The attention is paid to absence in the state of certain discretion which comes down to possibility of selection of remedy for performance of their obligation. Attention is paid to comparison of provisions of legal acts of Ukraine, which determine material and legal remedies of civil rights with Article 13 of Convention and practice of European court. Practice of application by national courts of Ukraine of unnamed remedies of protection of subjective rights and legally protected interests has been researched.